Three-step method for proliferation and differentiation of human embryonic stem cell (hESC)-derived male germ cells. - Jung Jin Lim; Myung Sun Shim; Jeoung Eun Lee; Dong Ryul Lee (PLoS ONE, 2014)
The low efficiency of differentiation into male germ cell (GC)-like cells and haploid germ cells from human embryonic stem cells (hESCs) reflects the culture method employed in the two-dimensional (2D)-microenvironment. In this study, we applied a three-step media and calcium alginate-based 3D-culture system for enhancing the differentiation of hESCs into male germ stem cell (GSC)-like cells and haploid germ cells. In the first step, embryoid bodies (EBs) were derived from hESCs cultured in EB medium for 3 days and re-cultured for 4 additional days in EB medium with BMP4 and RA to specify GSC-like cells. In the second step, the resultant cells were cultured in GC-proliferation medium for 7 days. The GSC-like cells were then propagated after selection using GFR-α1 and were further cultured in GC-proliferation medium for 3 weeks. In the final step, a 3D-co-culture system using calcium alginate encapsulation and testicular somatic cells was applied to induce differentiation into haploid germ cells, and a culture containing approximately 3% male haploid germ cells was obtained after 2 weeks of culture. These results demonstrated that this culture system could be used to efficiently induce GSC-like cells in an EB population and to promote the differentiation of ESCs into haploid male germ cells.